The Fortepiano in France, 1770–1815: Instruments, Sources, and Repertoire - Montebugnoli, Luca (Paris, France La Nouvelle Athènes - Centre du piano romantique and Centre de Musique Baroque de Versailles (CMBV), 2024)
This presentation traced the early development of French pianism and piano making between 1770 and 1815, with a focus on the emergence of a distinct French aesthetic. It combined the study of historical instruments—particularly those by makers such as Erard Frères—with an analysis of pedagogical sources, genres, and the work of major composers active during the period. Through this multifaceted approach, the presentation identified the stylistic features and cultural contexts that shaped French pianistic identity at the turn of the nineteenth century.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850